Stepper motor control for single axis solar tracker based on Arduino - Saputri, Riza; Pulungan, Ali Basrah (Department of Electrical Engineering Universitas Negeri Padang, 2025)
The need for electrical energy continues to increase along with technological developments, so the utilization of solar energy as an alternative source is important. However, the efficiency of solar panels is greatly affected by the angle of incidence of sunlight which changes due to the rotation of the earth. To overcome this problem, a solar tracker is used. Solar tracker is a system designed to optimize the absorption of solar energy by adjusting the position of solar panels to keep them facing the direction of incoming sunlight. This research develops a stepper motor-based one-axis solar tracker to increase the efficiency of solar energy absorption. The system uses five main tracking positions that are adjusted to the movement of sunlight in the equatorial region. The stepper motor control is implemented using Arduino IDE and uses G-code program to simplify programming, while Real Time Clock (RTC) is used for scheduling automatic movement based on time. Results show the system has high accuracy in its positional displacement, making it an effective solution for tropical applications.